Dynamic propagation area to simulate soft tissue de-formations using mass spring method - Mohd Nadzeri, Omar; Muhammad Hilmi, Jalil (Springer Nature Singapore Pte Ltd., 2022)
Modeling soft tissues during deformation is a real challenge in the development of a surgical simulation. Modeling techniques must be able to model deformations accurately in real-time interactions. Mass Spring Method (MSM) is one of the well-used modeling techniques. Most MSM models were developed via force propagation, where the definition of the propagation area is crucial for realism and optimum computational efficiency. In this paper, a new technique for establishing the area of propagation is proposed in which the area of propagation is determined by identifying a distance from contact point where minimum displacement occurs. The distance is calculated using the Boussinesq equation, which considers the material properties and the magnitude of the subject load. Implementation of the proposed method and validation with Finite Element Method (FEM) assessments show that the proposed method provides better rationale for the area of propagation and optimized computational efficiency.